Um animal que se autointerpreta: a articulação entre ontologia, história e política na filosofia de Charles Taylor - Ribeiro Filho, Marcos Aurélio Pensabem (2024)
This study intends to explain how ontology, history and politics are linked to the thesis of the human as a self-interpreting animal in Charles Taylor's philosophy. To this end, the theme will be developed in three parts. In the first and second chapters, the study focuses on Taylor's ontological analysis, understood as an investigation of the hermeneutic conditions of the way in which human beings realize themselves in the world. In other words: an analysis of the characteristic elements necessary for all meaningful human action. In the third chapter, the study is dedicated to discussing how the ontological-anthropological thesis defended by Taylor is historical and therefore needs a narrative foundation. Thus, we try to reconstruct the conception of history underlying the historical narrative that provides argumentative support for the thesis of the human as a self-interpreting animal. Finally, in the fourth and last chapter, the research consists of explaining how Taylor's conception of the political-secular is in line with and interconnected to both his narrative reconstruction of Modernity and his anthropological-hermeneutic thesis. Through this argumentative approach, we try to explain the intertwined way in which ontology, history and politics are articulated in Taylor's thesis of the human as a self-interpreting animal.